Analisis Perubahan Makna Meluas (Generalisasi) pada Media Sosial Facebook - Yeremias Bardi; Katharina Woli Namang; Amina Dewi; Trisnawati Bura (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
Semantic is the science of the meaning of language. In this case, widespread change in meaning relating to the use of the word. Widespread change in meaning is a change that occurs in a word that lacks only one meaning. This research is motivated by language which aims to meet the needs in communication. The issues discussed are a form of widespread change of meaning (generalization) on Facebook's social media. The purpose of this study was to determine, describe the form of widespread meaning changes found on Facebook's social media. This research is a qualitative descriptive research. The source of data in this study is Facebook's social media and sources or journals researching about Meaningful Changes (Generalization) on Facebook's Social Media Objects analyzed, namely the Changes in Widespread Meaning (Generalization) at Facebook's Social Media. The data collection techniques in this study are the author using Literature Study, please note. The researcher listened and noted the words experiencing changes in meaning found on the status and comments on Facebook as well as documentation.Lang measures in the study were identifying words with changes in meaning, noting identification, conducting data collection and processing conclusions and drawing conclusions. From the results of the discussion, there are 8 (Eight) forms of widespread meaning found.